Listening to grass-hoppers : field notes on democracy - Roy, Arundhati (Hamish Hamilton an imprint of Penguin Books, 2009)
With special reference to various topics related to anti-democratic issue of communalism, division between Muslims and Hindus, state sponsored terrorism, terrorist attacks, and emergence of Hindutva in India; articles previously published in several journals and books.